PENGARUH BRAND TRUST, BRAND AWARENESS DAN CUSTOMER REVIEW TERHADAP KEPUTUSAN PEMBELIAN PADA LAZADA DI KOTA BATAM. - Iwan Andrianto; Suhardi Suhardi (SCIENTIA JOURNAL, 2025)
This study aims to determine Brand Trust, Brand Awareness and Customer Review on Purchasing Decisions on Lazada in Batam City. This study used quantitative techniques. The sampling technique used the lemeshow formula totaling 100 respondents with Purposive Sampling technique. Data collection was done by distributing questionnaires via Google Form. Descriptive statistical tests, data quality tests, classical assumption tests, influence tests, and hypothesis tests were carried out using the SPSS 29 program. The results of multiple linear analysis on the Brand Trust variable have an influence on Purchasing Decisions. The Brand Awareness variable has an influence on Purchasing Decisions. and the Customer Review variable has an influence on Purchasing Decisions. The coefficient of determination (R2) shows that Brand Trust, Brand Awareness, and Customer Review together can explain Purchasing Decisions. The t-test shows that Brand Trust, Brand Awareness, and Customer Reviews have an influence on Purchasing Decisions